The real teacher arrives: toward a modern education of children and adults - Saar, Sven (Frontiers in Education, 2023)
In this article I will examine the role of traditional paradigms in developing systematic education. I will then offer a modern alternative, expanding on the question what learners need from their teachers and focusing on the gestures of intention, implementation, and impact. Finally, I will look at how Teacher Education can respond to the changed and changing needs of modern learners. Here, the holistic Steiner/Waldorf approach offers a particularly attractive alternative to mainstream Teacher Education in its focus on the self-education of the teacher.